THE ROLE OF SOCIAL COMMUNITIES IN THE IMPLEMENTATION OF ZISWAF FOR THE WELFARE OF COMMUNITIES (STUDY IN THE SAVE_ID COMMUNITY IN TEGAL REGENCY) - Hakim, Lukmanul (Proceeding International Seminar of Islamic Studies, 2023)
The role of ZISWAF is crucial in economic, social, cultural and educational growth in Indonesia. During the post-pandemic recovery period, as it is today, it is hoped that Muslims who have more assets can ease the burden on their brothers and sisters in the form of ZISWAF. ZISWAF distribution can be done through social communities, one of these social communities is the Save_Id community which is active in the spiritual, economic and social fields. This study aims to determine the role of the Save_Id social community in implementing the ZISWAF program in the people of Tegal Regency. This research uses a qualitative descriptive method, and data collection through observation, interviews and documentation of activities were analyzed using a deductive method. The study results explain that the Save_Id social community plays an essential role in the welfare of people in need during a pandemic and post-pandemic by receiving and distributing ZISWAF funds through several social activities that have been carried out. This research also fosters a sense of public trust in the social community, encouragement to society to be more productive, and play an active role in improving Indonesia's post-pandemic economy.Keywords: Community Welfare, The Role of the Save_Id Community, ZISWAF